Pharmacological evaluation of Dactyloctenium aegyptium: An indigenous plant used to manage gastrointestinal ailments (Bangladesh Journal of Pharmacology, 2015)
Crude extract of Dactylotenium aegyptium and its fractions were evaluated to rationalize its folkloric use in gastrointestinal ailments. In spontaneous contracting rabbit jejunum preparation, D. aegyptium exert concentration-dependent spasmogenic effect (0.01-0.1 mg/mL) followed by spasmolytic effect at higher doses (0.3-3.0 mg/mL). Pretreatment of the tissue preparations with atropine resulted in suppression of the spasmogenic response. Furthermore, D. aegyptium (1.0 mg/mL) caused relaxation of K+ (80 mM)-induced spastic contractions in isolated rabbit jejunum preparations and there was non-parallel shift in Ca++ dose response curves towards right (0.1-0.3 mg/mL). These findings were found to be comparable with verapamil, a standard Ca++ channel blocker. The solvent-solvents fractionation reflected segregations of spasmogenic and spasmolytic effects in respective aqueous and dichloromethane fractions. The above-mentioned findings reflected, presence of cholinergic as well as Ca++ channel blocking activity in ethanolic extract of D. aegyptium thus providing scientific basis for its folkloric use in constipation and diarrhea.